KEDUDUKAN SURAT EDARAN MAHKAMAH AGUNG BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Prasetya, Vestwansan Dipa; Indra, Mexsasai; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Circular Letter itself is a policy regulation for several reasons, as seen from its form, Circular Letters do not have a formal form that is similar to laws and regulations in general. Generally, legislation has forming parts such as Naming, Opening, Body, and Closing. We have not found these parts in a Circular so that from the formal point of view we can assume that the Circular is not a statutory regulation. Second, in terms of naming